Langerhans Cell Histiocytosis in the Chest Wall - Çakmak, Muharrem; Dağlı, Adile Ferda (My University, 2021)
Langerhans Cell Histiocytosis (LCH) refers to a non-\rneoplastic proliferation of Langerhans cells with an\rincidence in the adult population of 1–2 per million.\rIt is considered a pediatric disease, and while rib\rinvolvement is very rare, we report here on a 33-\ryear-old patient with LCH located in the rib.
Keywords: Onkoloji; Cerrahi